A numerical study on striped lithiation of tin oxide anodes. (1st March 2019) - Ramasubramanian, Ajaykrishna; Yurkiv, Vitaliy; Nie, Anmin; Najafi, Ali; Khounsary, Ali; Shahbazian–Yassar, Reza; Mashayek, Farzad
Highlights: A continuum scale model to simulate lithium ion intercalation in a battery's SnO2 electrodes is developed. The model hypothesizes that stripes are formed as an effect of the surface stress due to the uneven contact of the source on the nanowire (NW). The results from the developed model capture the experimentally observed striped lithiation due to the induced stresses, at low concentrations of Li. The developed predictive model is used to provide more insight into the microstructural evolution, morphological changes, and mechanical degradation in SnO2 electrodes. Abstract: High energy storage capacity of tin oxide (SnO2 ) makes it a promising anode material for high capacity lithium (Li)-ion batteries. Previous experiments reported by Nie et al. (2013) and Huang et al. (2010) have shown that SnO2 lithiation occurs in two stages. First, Li diffuses rapidly through distinct narrow stripes along the electrode axis. This is followed by a second stage where the diffusion/amorphization of the nanowire occurs. In order to understand and possibly predict this complex chemo-mechanical phenomenon, a finite element (FE) model is developed in this work. The model captures the formation of the striped diffusion regime and the corresponding expansion of the nanowire during the lithiation of SnO2 . The effect of the stress on the Li diffusion is modeled at the macroscopic level by implementing a stress-dependent expression for the diffusion coefficient. The modeling results clearly show the formation of the striped diffusion regime due to the induced stresses, at low concentrations of Li. This results in a small strain of 0.017 within the nanowire followed by a bulk diffusion and expansion at higher Li concentrations. Thus, the model allows for the spatiotemporally resolved analysis of Li diffusion/intercalation and helps predicting its influence on the mechanical performance of the electrode under the realistic operational conditions.